Combining Biomimetic Block Copolymer Worms with an Ice‐Inhibiting Polymer for the Solvent‐Free Cryopreservation of Red Blood Cells. (28th January 2016) - Mitchell, Daniel E.; Lovett, Joseph R.; Armes, Steven P.; Gibson, Matthew I.
Abstract: The first fully synthetic polymer‐based approach for red‐blood‐cell cryopreservation without the need for any (toxic) organic solvents is reported. Highly hydroxylated block copolymer worms are shown to be a suitable replacement for hydroxyethyl starch as a extracellular matrix for red blood cells. When used alone, the worms are not a particularly effective preservative. However, when combined with poly(vinyl alcohol), a known ice‐recrystallization inhibitor, a remarkable additive cryopreservative effect is observed that matches the performance of hydroxyethyl starch. Moreover, these block copolymer worms enable post‐thaw gelation by simply warming to 20 °C. This approach offers a new solution for both the storage and transport of red blood cells and also a convenient matrix for subsequent 3D cell cultures.